A Systematic Review and Meta-Analysis of Paracervical Blocks as A Perioperative Strategy in Reducing Postoperative Pain in Patients Undergoing Laparoscopic Hysterectomy - Nabiel, Rifaldy; Suseno, Daniel Alexander; Hadisubroto, Yonas; Gemawan, Taufiq; Anindito Putri, Aurellia Nuraini; Salsabila, Syadza; Sari, Eprila Darma (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Perioperative strategies to reduce postoperative pain are important for enhancing patient satisfaction. However, further research and trials has sparked ongoing debates of various strategies regarding efficacy and safety. Objective: This study aims to improve evidence-based strategies regarding the effect of paracervical anaesthetic blocks in patients undergoing laparoscopic hysterectomy. Methods: A systematic literature search was conducted through PubMed, Google Scholar, and ScienceDirect for RCTs in laparoscopic hysterectomy patients administered paracervical blocks and those given placebos. The quantitative analysis of pooled relative risk and mean difference with a 95% confidence interval were performed using the Review Manager 5.4 software in the random-effects model or fixed-effects model forest plot. Results: Based on four RCTs included in the analysis, there were significant differences in overall postoperative pain scores assessed by VAS (Visual Analogue Scale) [MD = -0.82, 95%CI (-1.47 to -1.06), p = 0.01]. The subgroup analysis also showed significant differences in VAS pain scores at 30 min and 1 hour post-operation [MD = -2.13, 95% CI (-3.09 to -1.16), p = 0.0001] and [MD = -2.55, 95% CI (-4.29 to -0.81), p = 0.004]. However, there were insignificant results in adequate pain control [RR = 7.90, 95%CI (0.39 to 158.67), p = 0.18], length of hospital stay [MD = 0.01, 95%CI (-0.52 to 0.54), p = 0.96], additional analgesics requirement at 24 hours [RR = 0.88, 95%CI (0.55 to 1.39), p=0.58], and perioperative complications [RR = 0.90, 95%CI (0.56 to 1.47), p = 0.68].Conclusion: This meta-analysis provides evidence that the administration of paracervical block in patients undergoing laparoscopic hysterectomy is associated with a reduction of postoperative VAS pain score but not associated with the length of hospital stay, adequate pain control, additional analgesics requirement at 24 hours, and perioperative complications.